If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -66 = 7x + 34 Reorder the terms: -66 + 11x = 7x + 34 Reorder the terms: -66 + 11x = 34 + 7x Solving -66 + 11x = 34 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -66 + 11x + -7x = 34 + 7x + -7x Combine like terms: 11x + -7x = 4x -66 + 4x = 34 + 7x + -7x Combine like terms: 7x + -7x = 0 -66 + 4x = 34 + 0 -66 + 4x = 34 Add '66' to each side of the equation. -66 + 66 + 4x = 34 + 66 Combine like terms: -66 + 66 = 0 0 + 4x = 34 + 66 4x = 34 + 66 Combine like terms: 34 + 66 = 100 4x = 100 Divide each side by '4'. x = 25 Simplifying x = 25
| 5gf^2+g^2f+15gf= | | 9(2p-1)= | | 9t=-2t^3-9t^2 | | 4y^2-18y+21=0 | | 7x+18=4x+30 | | 43-[4+9y-3(y+5)]=-5(2y+3)-[6(y-1)-3y+2] | | 31792.5=3.14*r^2 | | 36=-4(x-3) | | 2n^2=-24-19n | | y+7x=28 | | 4(7x)+8(4y)-3(5x)+2x+5y+x-7-5-10y= | | 5br-25b+2r-10= | | cosx=0.3x | | 3=8d-13 | | 20t-9.8t^2=0 | | 4(4)+a*a=5 | | 6(a-2)=9a-3(2a-1) | | -56+5x=-4x+52 | | y=zx+2 | | 12x-61=7x+64 | | 2x+x+2(2)+47=180 | | 10(s-3)=-131 | | x-59=53-3x | | 8cos^2(x)+4cos(x)-5=0 | | 9+3x-18=0 | | 1.4+2x=0 | | 5xy=xsquared | | 2x+x+2(2)+19=180 | | -4=y-65 | | x-9y=-14 | | 3(3x-1)=8(x+1) | | 13x-11=-180 |